2018
DOI: 10.1002/star.201700290
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fluidized Bed Jet Milling on Structural and Functional Properties of Normal Maize Starch

Abstract: Normal maize starch samples with moisture contents of 11.24%, 6.18%, and 1.5% are ground using a fluidized bed jet mill at classifier frequencies of 2400, 3000, 3600, and 4200 to produce micronized starch powder. The changes in structural and functional properties of the starch after jet milling process are studied. The particle size of starch significantly (p < 0.05) decreases after jet milling and as the classifier frequency increases. Also, the bulk and tap density decreases; while the specific surface area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…After ultrasonic treatment for 1 min, the surfaces of some starch granules became rough and small fragments flaked off on the surfaces (Figure B). After ultrasonic treatment for 8 min, the free vibration amplitude of starch molecules improved and the surface activity of starch granules increased (Wang et al, ). Therefore, starch granules with higher surface activity tended to aggregate, so some bulges formed on the surfaces at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…After ultrasonic treatment for 1 min, the surfaces of some starch granules became rough and small fragments flaked off on the surfaces (Figure B). After ultrasonic treatment for 8 min, the free vibration amplitude of starch molecules improved and the surface activity of starch granules increased (Wang et al, ). Therefore, starch granules with higher surface activity tended to aggregate, so some bulges formed on the surfaces at this stage.…”
Section: Resultsmentioning
confidence: 99%
“…Starch granules with low surface area exhibited higher swelling capability probably due to the presence of phosphate groups and absence of lipids on the granule surface. Wang et al () found that jet‐milling of normal maize starch led to the increase in mean weight specific area followed by the increase in pasting temperature caused by the destruction of starch, decrease in particle size and weaker intramolecular interactions of starch dispersed in water. On the contrary, it was established that amylose content had major influence on pasting temperature than granule size and phosphorus content using multiply linear regression analysis of 105 potato starch samples (Zaidul et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…The granular material is fed to the cylindrical grinding chamber (6) gravitationally from the charging container (8). The fed material undergoes extensive fluidization employing air jets from the nozzles (5). The nozzles inject air concentrically at a controlled flow rate and overpressure p with flow velocity u.…”
Section: Subject Of Researchmentioning
confidence: 99%
“…It depends on many parameters, such as different physical and chemical properties of the material being ground: homogeneity, strength, hardness, humidity, viscosity, forces and stresses occurring in said particles, internal particle structure, material defects of ground particles, and mill construction. A random occurrence often characterizes these variables [ 1 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation